A revision of the ahermatypic Scleratinia of the Galapagos and CocosIslands. - Cairns, Stephen D. (Washington, D.C. Smithsonian Institution Press, 1991)
Smithsonian Contributions to Zoology; No. 504
Keywords: Scleractinia--Galapagos Island--Classification.; Scleractinia--Cocos(Keeling)Islands--Classification.; Scleractinia--Galapagos Islands--Geographic distribution